2020
DOI: 10.1088/1741-4326/abac6b
|View full text |Cite
|
Sign up to set email alerts
|

3D transient CFD simulation of an in-vessel Loss-Of-Coolant Accident in the EU DEMO fusion reactor

Abstract: Accidental transients in fusion reactors, such as the in-vessel Loss-of-Coolant Accident (LOCA) considered here, are generally analyzed using system-level codes. However, because of their lumped nature, such tools cannot predict local pressure and temperature values, which are instead of interest to assess the integrity of the Vacuum Vessel (VV) structures. It is then fundamental to prove that the system-level tools' predictions are at least conservative. In this work, we analyze the helium flow inside the VV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Meanwhile, the comparison of different turbulence results shows that the velocity distribution in the range of 0-600 m s −1 and the Mach number distribution in the range of 0-3 simulated by the k-w SST turbulence model are more similar to the results simulated by Uchibori et al [14]. Thus, the applicability of the model applied in this study to the underexpanded jet is qualitatively As shown in figure 6, the changes in pressure on the jet center line of different turbulence models are simulated and compared with the results of Uchibori [14], Zappatore [10], and experimental data of Kuehner [15] and Woodmansee [16]. Figure 6 shows that the pressure on the jet center line decreases with underexpansion and increases sharply with the generation of shock waves at the Mach number disk, so all results show a trend of first decreasing and then increasing.…”
Section: Verification Of Model Applicabilitysupporting
confidence: 80%
See 3 more Smart Citations
“…Meanwhile, the comparison of different turbulence results shows that the velocity distribution in the range of 0-600 m s −1 and the Mach number distribution in the range of 0-3 simulated by the k-w SST turbulence model are more similar to the results simulated by Uchibori et al [14]. Thus, the applicability of the model applied in this study to the underexpanded jet is qualitatively As shown in figure 6, the changes in pressure on the jet center line of different turbulence models are simulated and compared with the results of Uchibori [14], Zappatore [10], and experimental data of Kuehner [15] and Woodmansee [16]. Figure 6 shows that the pressure on the jet center line decreases with underexpansion and increases sharply with the generation of shock waves at the Mach number disk, so all results show a trend of first decreasing and then increasing.…”
Section: Verification Of Model Applicabilitysupporting
confidence: 80%
“…In order to verify the effectiveness of the above solution model in the underexpanded jet, the flow under the same conditions as those in [10,[14][15][16] was simulated by ANSYS Fluent code, and the simulation results were compared with them. Figure 3 shows the geometric model of the verification simulation, and the pressure difference between the inside and outside of the model is large.…”
Section: Verification Of Model Applicabilitymentioning
confidence: 99%
See 2 more Smart Citations